Rotator cuff regeneration using a bioabsorbable material with bone marrow-derived mesenchymal stem cells in a rabbit model - Yokoya, Shin; Mochizuki, Yu; Natsu, Koji; Omae, Hiromichi; Nagata, Yoshihiko; Ochi, Mitsuo (The American journal of sports medicine, 2012)
Rotator cuff regeneration using tissue engineering techniques is a challenging treatment in elderly patients with irreparable rotator cuff tears. A polyglycolic acid sheet scaffold with seeded mesenchymal stem cells (MSCs) may enhance the expression of type I collagen products and increase the mechanical strength of the regenerated tendon in vivo. Controlled laboratory study. A surgically created defect of infraspinatus tendons of rabbits was reconstructed with 2 different materials, a polyglycolic acid (PGA) sheet alone (PGA group) (n = 34) and a PGA sheet seeded with autologously cultured MSCs (MSC group) (n = 34). The authors created a tendon defect model without embedding any graft as the control model (control group) (n = 34). The rabbits were sacrificed at 4, 8, and 16 weeks after the operation and then were histologically evaluated. The rabbits were also biomechanically evaluated by measuring the ultimate failure loads and Young's modulus at 4 and 16 weeks following implantation. In the MSC group, the fibrocartilage layers and Sharpey fibers were found regularly in the insertion site at 8 weeks compared with the PGA group. In control group, thin membranes with many fibroblasts arranged in an irregular pattern linked the end of the torn cuff to the bone without any Sharpey fibers and type I collagen. A large volume of type I collagen was found in comparison with type III collagen at 16 weeks in the MSC group, whereas type III collagen was more prevalent than type I in the PGA group. The tendon maturing score in the MSC group had higher values than the PGA and control groups at 8 and 16 weeks (mean values were 21.0 ± 0.89, 24.0 ± 2.53 in the MSC group; 16.7 ± 2.25, 21.3 ± 2.42 in the PGA group; and 10.2 ± 0.98, 12.2 ± 1.72 in the control group, respectively) (P < .05). The results of the mechanical analysis revealed that the regenerated tendons in the MSC group had better tensile strength than in the PGA and control groups at 16 weeks (mean values were 3.04 ± 0.54 in the MSC group, 2.38 ± 0.63 in the PGA group, and 1.58 ± 0.13 in the control group) (P < .05). Bone marrow-derived MSCs were able to regenerate tendon-bone insertions and the tendon belly, including the production of type I collagen, and increased the mechanical strength of the regenerated rotator cuff tendon. Rotator cuff regeneration using MSCs is a promising treatment for massive rotator cuff defects.